Assessing techniques to successfully monitor the oceanography of the complex uThukela Marine Protected Area - Ramsarup, Neha (Department of Oceanography, 2023)
Marine Protected Areas (MPAs) are increasingly being established to restore and protect coastal and marine environments. The newly established uThukela Marine Protected Area (MPA), located on the central KwaZulu-Natal Bight along the northeast coast of South Africa, has been identified as a key ecological region. The region provides recruitment and is a general nursery area for marine life on the Bight. Knowledge of the oceanographic dynamics in the region is essential for understanding the functioning of the ecosystem and the effectiveness of the MPA. This study analysed changes in ocean temperatures at 20 sites along the Bight over a 41-year period using in situ beach and UTR data, and satellite data. Significant warming of 0.03°C/year occurred at beach sites within and around the MPA. Beach temperatures increased at an average rate of 0.02°C/year across the Bight, during both summer and winter, whereas UTR temperatures warmed by 0.14°C/year during summer and 0.08°C/year during winter. At the event scale, a case study of a persistent decrease in in situ temperatures along the entire Bight during summer 2017/2018 was investigated. The decrease in temperatures was hypothesised to be as a result of the combined effects of a La Niña event and a Natal Pulse, which could have significant consequences for temperature-sensitive species. Temperature trends observed in beach temperatures over the 41 years were not reflected in beach temperatures over the past decade, highlighting the importance of large datasets when investigating climate change. Warm biases of up to 2°C observed in satellite-derived temperature measurements, and its failure to replicate trends seen in the beach data, suggests that in situ temperature measurements in MPAs are better suited for long-term monitoring efforts. These findings can help assess the success of MPAs and to guide monitoring and research activities within the region.